(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract. The article presents a review of modern approaches to the selection of surgical tactics in complicated forms of acute cholecystitis. The main clinical factors influencing the choice of surgical intervention are analyzed, including the severity of inflammation, anatomical features, comorbid conditions, and the timing from disease onset. Indications for laparoscopic, open, and subtotal cholecystectomy, as well as for the use of percutaneous cholecystostomy, are discussed. The importance of an individualized approach is emphasized, which allows a reduction in postoperative complications and improvement of treatment outcomes in patients with complicated acute cholecystitis.